2015
DOI: 10.1007/s00705-015-2462-7
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium circinatum isolates from northern Spain are commonly infected by three distinct mitoviruses

Abstract: Pitch canker is a serious disease of pines caused by the ascomycete fungus Gibberella circinata (anamorph = Fusarium circinatum). Three distinct mitovirus strains have been described in this fungus: Fusarium circinatum mitovirus 1 (FcMV1), FcMV2-1 and FcMV2-2. Here, we investigated the frequency and population variation of these viruses and closely related sequence variants in northern Spain using RT-PCR and sequencing. Each virus strain and similar sequence variants shared >95 % sequence identity and were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
4
26
0
Order By: Relevance
“…Two paired monosporic cultures (mycovirus- infected and mycovirus-free) were used per isolate (Table 1). The presence of different mycovirus strains in each isolate was reported in a previous study by our research group (Vainio et al, 2015). In the present study, the presence or absence of mycoviruses (FcMV1 and/ or FcMV2-2) was confirmed according to Martínez-Álvarez et al (2014b).…”
Section: Fungal Isolatessupporting
confidence: 82%
See 1 more Smart Citation
“…Two paired monosporic cultures (mycovirus- infected and mycovirus-free) were used per isolate (Table 1). The presence of different mycovirus strains in each isolate was reported in a previous study by our research group (Vainio et al, 2015). In the present study, the presence or absence of mycoviruses (FcMV1 and/ or FcMV2-2) was confirmed according to Martínez-Álvarez et al (2014b).…”
Section: Fungal Isolatessupporting
confidence: 82%
“…The effects of mycoviruses on spore production and pathogenesis have also been widely reported (Kazmierczak et al, 1996;Wang et al, 2014, Zamora et al, 2016, indicating the potentially damaging effects of the viruses on plant health. Three different species of the genus Mitovirus that infect F. circinatum have recently been identified as putative members of Narnaviridae (genus Mitovirus) and designated Fusarium circinatum mitovirus 1, 2-1 and 2-2 (FcMV1, FcMV2-1 and FcMV2-2) (Martínez-Álvarez et al, 2014a;Vainio et al, 2015;Muñoz-Adalia et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The cDNA was used as a template for PCR with the following virus-specific primers: FMC1F1 (5 -CGTGGATTAAAACCCACAAA-3 ), FMC1Rev1 (5 -TGGTAATCTACCATAGCAATTAYTC-3 ), FMC3F1 (5 -GAYAGAACTTTTACTCAAGATCC-3 ) and FMC3Rev1 (5 -ATTCATCTYTTGGCAAATTCATA-3 ) [16]. The primer pair FMC1F1/FMC1Rev1 was specific to FcMV1, whereas FMC3F1/FMC3Rev1 was used to detect FcMV2-2.…”
Section: Total Rna Extraction and Pcrmentioning
confidence: 99%
“…These mitoviruses are common in F. circinatum isolates from northern Spain. They have been shown to be polymorphic [16] and their viral genome has recently been studied [17]. The main aim of the present study was to investigate how the probability and rate of transmission of these mitoviruses via microconidia vary in relation to the fungal isolate and strain of virus (FcMV1 and FcMV2-2).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium circinatum hosts several species and types of mitoviruses (Martínez‐Álvarez et al ., ; Vainio et al ., ), but the role the viruses play in pathogen virulence is not clear. While virulence of F. circinatum was enhanced on 1‐year‐old P. radiata seedlings (Muñoz‐Adalia et al ., ), mycelial growth of F. circinatum colonies and spore germination were significantly reduced by the virus presence under in vitro conditions (Flores‐Pacheco et al ., ).…”
Section: The Use Of Biological Control For Combating F Circinatummentioning
confidence: 99%